Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14202/vetworld.2018.209-214
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of probiotics and prilled fat supplementation on immune genes expression and lymphocyte proliferation of transition stage Karan Fries cows

Abstract: Background and Aim:Probiotics are the living microorganism which when administered improves the digestion and health of the animal. Saccharomyces cerevisiae (SC) improves the humoral and innate immunity of the animal. Prilled fat is a hydrogenated palm oil triglyceride which has been reported to promote the release of cytokines from macrophages. The aim of the study was to evaluate the immunomodulatory effect of probiotic and prilled fat during transition stage in Karan Fries (KF) cows.Materials and Methods:A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In our study, both PA and BHBA induced oxidative stress, increasing mRNA levels of inflammatory factors IL-8, IL-6, and TNF-α. We therefore evaluated levels of IL-8, IL-6, and TNF-α proteins by ELISA, revealing similar trends, which suggested that PA and BHBA promote inflammation, consistent with previous studies [41,42]. NAC, a commonly used antioxidant, exerts anti-oxidative activity and protects cells by scavenging oxygen free radicals under oxidative stress damage [43].…”
Section: Discussionsupporting
confidence: 84%
“…In our study, both PA and BHBA induced oxidative stress, increasing mRNA levels of inflammatory factors IL-8, IL-6, and TNF-α. We therefore evaluated levels of IL-8, IL-6, and TNF-α proteins by ELISA, revealing similar trends, which suggested that PA and BHBA promote inflammation, consistent with previous studies [41,42]. NAC, a commonly used antioxidant, exerts anti-oxidative activity and protects cells by scavenging oxygen free radicals under oxidative stress damage [43].…”
Section: Discussionsupporting
confidence: 84%
“…Improved nutrient digestion and enhanced cecal microbial population were observed in broilers by adding probiotics [85]. Enhanced immunity was recorded by several studies by the probiotic administration in poultry [86][87][88][89]. In the studies of Zhang et al [90], improved chicken growth rate, immune system, and antioxidant quantity were observed by the addition of Lactobacillus casei, and Bifidobacterium in the food.…”
Section: Probiotics In Poultry Productionmentioning
confidence: 98%
“…Probiotics have been proven to enhance immunity in ruminants owing to their immunostimulatory properties (Punetha et al, 2018). The regulation of immune system is by gene expression, stimulation of immune cells action, such as epithelial cells and dendritic cells, natural Killer T cells, and B cells, and controlling the signal process in host cells through the usage of probiotics (Begum et al, 2021).…”
Section: Probiotics and Immunomodulatory Rolementioning
confidence: 99%